Consanguineal and Affinal Kinship in the Sasak Language of Karang Bayan - Agustina, Dewi; Syamsurrijal; Miswaty, Titik Ceriyani; Syahid, Agus (Lexeme : Journal of Linguistics and Applied Linguistics, 2026)
This study aims to identify and classify the kinship terms used by the Sasak ethnic community in Karang Bayan and to analyze the social functions of these terms within cultural and communicative contexts. Using a qualitative descriptive method with an ethnolinguistic and anthropolinguistic approach, data were collected through semi-structured interviews, participant observation, and documentation involving three generational groups: elders, adults, and youth. The findings reveal that the Sasak kinship lexicon in Karang Bayan consists of two major categories: consanguineal kinship (e.g., amaq, inaq, polong) and affinal kinship (e.g., semame, senine, mentoak mama). These terms not only denote familial relations but also serve as linguistic expressions of social values such as respect, hierarchy, and customary obligations. The usage of these terms reflects ethnic identity and functions as a mechanism for intergenerational transmission of cultural values. The study confirms the essential role of language in maintaining social structure and cultural identity among the Sasak people amid the pressures of modern change.